2018
DOI: 10.1002/jlb.4a0518-191r
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal influenza-specific effector CTLs retain elevated CD31 levels at the site of infection and have decreased IFN-γ production

Abstract: The underlying mechanisms that regulate neonatal immune suppression are poorly characterized. CD31 (PECAM1) is highly expressed on neonatal lymphocytes and is a known modulator of TCR signaling. To further characterize the role of CD31 in the neonatal CTL response, 3‐d and 7‐d‐old murine neonates were infected with influenza virus and compared to adults. The majority of the pulmonary viral‐specific CTLs in the 3‐d‐old murine neonate retain CD31 expression, whereas adult CTLs have decreased CD31 expression. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…During acute respiratory viral infection, 3‐day old murine neonates have an increased frequency of activated viral specific CD31 + CD8 + T cells within the lung at the peak of the lymphocyte response compared to 7‐day old neonates and adults . CD31 + neonatal viral‐specific CTLs exhibit reduced IFNγ production and proliferation .…”
Section: Tcr Inhibitory Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…During acute respiratory viral infection, 3‐day old murine neonates have an increased frequency of activated viral specific CD31 + CD8 + T cells within the lung at the peak of the lymphocyte response compared to 7‐day old neonates and adults . CD31 + neonatal viral‐specific CTLs exhibit reduced IFNγ production and proliferation .…”
Section: Tcr Inhibitory Moleculesmentioning
confidence: 99%
“…CD31 + neonatal viral‐specific CTLs exhibit reduced IFNγ production and proliferation . CD31 transcript levels are dramatically elevated in sorted CD31 + effector CTLs from neonatally infected mice, which indicate a preferential continued expression in neonatal CTLs, compared to naïve or adult effector T‐cell populations . In support of a differential regulation of CD31 expression between neonates and adult mice, CD8 + T cells expressing a transgenic TCR specific for the ova peptide SIINFEKL(OT‐I CD8 + T cells) were injected into hosts immediately prior to infection with ova‐peptide expressing L. monocytogenes (Lm‐ova).…”
Section: Tcr Inhibitory Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-day-old mice neonates are considered representative of late term human neonates of 22-26 weeks gestation [101,102]. Therefore, many infant influenza studies using the mouse model have studied mice in the neonatal phase 2-7 days post-birth which is actually modeling humans in the second trimester of development [102][103][104][105][106]. It has also been reported that the mouse immune makeup at two weeks postpartum most resembles that of the infant human [107], and thus many other infant mice model studies of influenza virus infection have been done at two weeks postpartum [107].…”
Section: Mouse Modelsmentioning
confidence: 99%
“…Respiratory tract inflammatory and infectious disease in infant children represents a significant burden to the healthcare system (1,2). A particular example is influenza virus infection, for which there is evidence of increased incidence of disease severity in infants, as compared to adults in humans and animal models (3,4). Classic theory suggests that adaptive immunity, predominantly the T cell immune response, is altered in infants in order to support self-tolerance, maternal tolerance, and tolerance to new developmental or environmental antigen (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%